Proceedings of the 32nd Coral Gables Conference : (World Scientific, 2004)
This volume contains papers by over 40 physicists that summarize and interpret the newest findings, and suggest future avenues to be explored. A number of new theoretical ideas are also presented, dealing with progress in understanding the dynamics and symmetries of strings and branes, renormalization in quantum field theory, possible Lorentz violation effects, and related problems. Ongoing and next generation gravitational and neutrino experiments are described, and the issues of unification are dealt with in the context of, and beyond, the standard model.